Community Learning Center Efforts in Lifelong Learning Campaign in Equality Education - Afri Khofifah; Mintarsih Arbarini; Sachin Gupta (Universitas Negeri Semarang, 2023)
The low socialization efforts and internalization of lifelong learning in equality education students have a negative impact on the sustainability of adult education and learning activities. This study aims to describe efforts to empower lifelong learning through equality education in community learning centers. The study used a descriptive qualitative approach, with nine participants consisting of six students, two teaching staff, and the head of the community learning centers. Data collection techniques include interviews, observation, and documentation. Data accuracy with source triangulation. Subsequent data were collected through the stages of data reduction, data presentation, and conclusion. The results of the study show that community learning center efforts in supporting lifelong learning include providing an understanding of lifelong learning that produces the expected impact, providing learning motivation to students who still need improvement, and guiding students to plan their future activities, these efforts still not evenly obtained by students and need development as well as guiding students to self-evaluate their learning progress which is still limited to evaluating understanding of the material in class. The research contributes to enriching insights and providing insight into lifelong learning campaigns through equality education so that educators can increase citizen knowledge about concepts and support further research.